Bond Strengths of Geopolymer and Cement Concretes - Sarker, Prabir (Trans Tech Publications, 2010)
Geopolymer is an inorganic alumino-silicate product that shows good bonding properties. Geopolymer binders are used together with aggregates to produce geopolymer concrete which is an ideal building material for infrastructures. A by-product material such as fly ash is mixed together with an alkali to produce geopolymer. Current research on geopolymer concrete has shown potential of the material for construction of reinforced concrete structures. Structural performance of reinforced concrete depends on the bond between concrete and the reinforcing steel. Design provisions of reinforced concrete as a composite material are based on the bond strength between concrete and steel. Since geopolymer binder is chemically different from Ordinary Portland Cement (OPC) binder, it is necessary to understand the bond strength between geopolymer concrete and steel reinforcement for its application to reinforced concrete structures. Pull out test is commonly used to evaluate the bond strength between concrete and reinforcing steel.This paper describes the results of the pull out tests carried out to investigate the bond strength between fly ash based geopolymer concrete and steel reinforcing bars. Beam end specimens in accordance with the ASTM Standard A944 were used for the tests. In the experimental program, 24 geopolymer concrete and 24 OPC concrete specimens were tested for pull out. The concrete compressive strength varied from 25 to 55 MPa. The other test parameters were concrete cover and bar diameter. The reinforcing steel was 500 MPa steel deformed bars of 20 mm and 24 mm diameter. The concrete cover to bar diameter ratio varied from 1.71 to 3.62. It was found from the test results that the failure occurred by splitting of concrete in the region bonded with the steel bar, in both geopolymer and OPC concrete specimens. Comparison of the test results shows that geopolymer concrete has higher bond strength than OPC concrete. This suggests that the existing design equations for bond strength of OPC concrete with steel reinforcing bars can be conservatively used for calculation of bond strength of geopolymer concrete.